The Contribution of Religiosity and Self-Efficacy toward Academic Cheating - Suhartati Wahyu; Dina Sukma (Journal of General Education and Humanities, 2026)
Academic cheating is a phenomenon that can compromise the integrity of education. It does not occur due to a single reason, but rather results from the interaction between academic environmental conditions and individual characteristics, including psychological and spiritual dimensions that serve as an individual's moral defense. These dimensions are self-efficacy and religiosity. This study aims to describe the profiles of academic dishonesty, religiosity, and self-efficacy, as well as to examine the contributions of religiosity and self-efficacy to student academic cheating. This research uses a quantitative approach with a descriptive-correlational method. The population consisted of students from the Faculty of Education, Universitas Negeri Padang (FIP UNP), from the 2024 intake. The sample was selected using a proportional random sampling technique, with the sample size determined by the Slovin formula. Data were collected using Likert scale questionnaires measuring religiosity, self-efficacy, and academic cheating. The data were analyzed using percentage descriptive statistics, while simple and multiple regression analyses were used to test the variables' contributions. The results of the study indicate that: (1) student religiosity is predominantly in the high category, (2) student self-efficacy is mostly in the moderate category, (3) student academic cheating is largely in the low category, (4) religiosity contributes negatively and significantly to academic cheating, (5) self-efficacy contributes negatively and significantly to academic cheating, and (6) religiosity and self-efficacy together contribute negatively and significantly to academic cheating. This means that higher levels of religiosity and self-efficacy correspond to a lower tendency among students to engage in academic cheating. These findings suggest that the combination of religiosity and self-efficacy serves as an effective internal strength to reduce intentions and behaviors of cheating within the academic environment. While religiosity plays a vital role in preventing academic cheating, self-efficacy has not been optimal, highlighting the need for strengthening efforts to ensure self-belief remains strong and unwavering.